Demonstration Method in Fiqh Learning of Thaharah Material to Improve Student Learning Outcomes at MTs Maraqitta'limat Gelumpang - Mulyadi (Indonesian Journal of Education and Social Humanities, 2025)
This study aims to determine the application of the demonstration method in learning fiqh material for taharah class VII at MTs Maraqitta'limat Gelumpang and to determine the application of the demonstration method can improve understanding and improve student learning outcomes for hajj material for class VIII at MTs Maraqitta'limat Gelumpang. This study is a classroom action research that uses four steps, namely planning, action, observation and reflection. The subjects of this study were students of class VIII MTs Maraqitta'limat Gelumpang. The data for this study were obtained using test and observation techniques. Tests are used to measure learning outcomes and observations are used to analyze teacher and student learning activities. The data analysis technique used in this study is descriptive statistics by comparing the results obtained with indicators of research success. The results of the study indicate that the application of the demonstration method can improve student understanding and learning outcomes. This can be seen from the results of the post-test from each cycle, namely cycle I (56.52%) and cycle II (86.95%), as well as the achievement of student scores that have reached the minimum completeness criteria.